Masticatory behavior for different solid foods in preschool children according to their oral state. Issue 3 (6th February 2019) - Linas, Natacha; Peyron, Marie‐Agnès; Hennequin, Martine; Eschevins, Caroline; Nicolas, Emmanuel; Delfosse, Caroline; Collado, Valérie
Abstract: Gradual introduction of solid foods in early childhood takes part in the maturation of mastication. The impact of any oral state alteration on food oral processing development is poorly documented for this age group. This study investigated the masticatory behavior in 3 to 6 year‐old children with or without early childhood caries (ECC) for three solid foods of different textures. Twenty‐one children with healthy oral state and 23 children with severe ECC were observed during complete mastication of calibrated samples of raw carrot, cheese and breakfast cereals. Food refusals and kinematic parameters (Ti: chewing time, Nc: number of cycles and Fq: chewing frequency) were used to assess children masticatory behavior. Oral Health‐related Quality of Life and orofacial dysfunctions were evaluated using, respectively the early childhood oral health impact scale (ECOHIS) and the Nordic orofacial dysfunction test screening (NOT‐S). Children suffering from ECC exhibited significantly higher ECOHIS and NOT‐S scores, in particular for the mastication domain. Accordingly, lower chewing frequencies values were recorded in children with ECC (i.e., carrot Fq: 1.21 ± 0.20 vs 1.35 ± 0.22, p ≤ 0.01), as well as more frequent refusals for carrots. Kinematic parameters were shown to be repeatable in all children for successive samples of the same food, and tended to vary depending on the proposed food. Some masticatory behavior regulation according to food properties could already be present in preschool children. Children with ECC developed alternative behavioral strategies to overcome feeding difficulties. Further studies should investigate food bolus properties according to oral health, as well as nutritional issues. Practical applications: During childhood, the way solid foods are processed in the oral cavity to be safely swallowed and then digested in available nutrients, is poorly documented. In this study, preschool children have been shown to repeatedly adapt their masticatory behavior to a given food. The collection of various food boli as recorded at the moment of swallowing could then be considered in further food bolus properties research investigations. Moreover, this study suggested that children with altered dentition modified their masticatory kinematic parameters and developed alternative strategies, including food or texture selection, to overcome their feeding difficulties. The development of a mastication evaluation protocol could help medical professionals to detect children masticatory deficiencies and then propose diet adaptations. Considering the importance of food diversity in mastication development and maturation, food industries may consider to develop a range of texture adapted foods for young children, especially designed to gradually rehabilitate the masticatory function.